2011
DOI: 10.1007/s10763-011-9322-z
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Empirical Evidence on Scaffolding for Science Education

Abstract: This content analysis of articles in the Social Science Citation Index journals from 1995 to 2009 was conducted to provide science educators with empirical evidence regarding the effects of scaffolding on science learning. It clarifies the definition, design, and implementation of scaffolding in science classrooms and research studies. The results show important cross-study evidence that most researchers have adopted a qualitative approach (67.44%), focused on learning context (72.09%), and used high school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 39 publications
7
44
0
12
Order By: Relevance
“…In this meta-analysis, only 10% of included outcomes were associated with fading, only 6% with adding, and 15% with fading/adding, which is consistent with prior research (Belland et al 2017;Lin et al 2012). Using a traditional meta-analysis approach would have rendered it difficult to compare the effects of fading, adding, and no customization.…”
Section: Implications For Scaffolding Designsupporting
confidence: 78%
See 2 more Smart Citations
“…In this meta-analysis, only 10% of included outcomes were associated with fading, only 6% with adding, and 15% with fading/adding, which is consistent with prior research (Belland et al 2017;Lin et al 2012). Using a traditional meta-analysis approach would have rendered it difficult to compare the effects of fading, adding, and no customization.…”
Section: Implications For Scaffolding Designsupporting
confidence: 78%
“…According to the meta-analysis reported by Belland et al (2017), in 65% of the included studies, there was no scaffolding customization. Moreover, Lin et al (2012) also pointed out a lack of a number of studies adopting fading function (9.3%) in a review of 43 scaffolding-related articles. This means that while many scholars maintained that fading is an important element of scaffolding (Collins et al 1989;Dillenbourg 2002;Puntambekar and Hübscher 2005;Wood et al 1976), scaffolding customization has largely been overlooked in scaffolding design.…”
Section: Moderators For Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some scholars suggested that interventions that do not include fading cannot be called scaffolding (Pea, 2004;Puntambekar & Hübscher, 2005). The count of outcomes in which scaffolding was faded or added versus when scaffolding was neither added nor faded indicated that the majority of outcomes were associated with no fading or adding (64.9 %), which is consistent with prior research (Lin et al, 2012;Pea, 2004;Puntambekar & Hüb-scher, 2005). But the meta-analysis suggests that scaffold customization does not influence cognitive outcomes.…”
Section: Scaffold Customizationsupporting
confidence: 76%
“…explicating critical or controversial positions) to reveal students' personal knowledge addressing a specific subject Beishuizen 2010, 2011;Wittwer and Renkl 2008). Students respond and show a degree of understanding, giving the teacher indications about what students know and think (Lin et al 2012;Ruiz-Primo and Furtak 2007). Aarkrog (2005) shows that it is difficult for students to learn from the expertise of their teachers since they have to personalize it.…”
Section: Teaching Strategies In Relation To Negotiation Of Meaningmentioning
confidence: 99%